M-cholinoreactivity dynamics in frog myocardium exposed to serum from human umbilical blood - V. I. Zirkin; A. N. Trukhin; E. N. Sizova; S. A. Dvorjanskiy (Российский кардиологический журнал, 2004)
In experiments with isolated hearts from 31 frogs (R. ridibunda), acetylcholine (10-7, 10-6, 10-5g/ml) in a dose-dependent manner reduced contraction amplitude during electrostimulation (30 s, 1 Gz, 5 ms, 5-10 W). The time to achieve maximal amplitude did not change, that meant the serum had negative inotropic effect, weakening chrono-inotropic correlations. Serum from umbilical blood in titer 1 : 100 (SUB-1: 100) did not affect contraction amplitude and chrono-inotropic correlations. But, due to endogenous blocker of M-cholinoreceptors (EMCRB), it decreased myocardial M-cholinoreactivity, demonstrating M-cholinoblocking properties. In particular, the serum shifted the dose-effect curve rightand downward, increasing acetylcholine Kd by more than 3 times. Serum acetylcholine affinity to M-CHR diminished, and M-cholinergic influence on the heart became less effective. The serum decreased acetylcholine potential (10-7 and 10-6 g/ml) to weaken chrono-inotropic correlations. In some cases, SUB-1: 100, due to endogenous M-cholinorecepor stabilizer (EMCRS), increased negative inotropic effect of acetylcholine. The nature of EMCRB and EMCRS, together with their possible normal and pathologic role in regulating the heart function, is discussed.